Fabric Selection for the Reference Clothing Destined for Ergonomics Test of Protective Clothing—Sensorial Comfort Point of View - Bartkowiak Grażyna; Frydrych Iwona; Komisarczyk Agnieszka; Greszta Agnieszka (AUTEX Research Journal, 2017)
The main purpose of this study is the selection of a proper fabric for the reference clothing for ergonomic tests of protective clothing. For research, seven fabric of different raw material content and different structure were chosen. We studied the handle of fabrics produced from blend of polyester/cotton and polyester/Tencel, which were designated by letters from A to G. The assessment of handle of the fabric was performed based on the mechanical properties of fabrics using Kawabata evaluation system (KES-system). It was proven that one of the tested fabrics (F) made of polyester and cotton fibers (85% PES / 15% cotton) with the reinforced twill weave is characterized by the highest total hand value (THV).The high THV results from the low value of koshi (stiffness) and the highest value of numeri (smoothness) and fukurami (fullness). However, in terms of physiological comfort, the lower value of fukurami is more preferred. It turned out that the fabric with the higher value of fukurami (including fabric F) is characterized by the lower air permeability and higher water vapor resistance. At the end, we decided that the reference clothing will be made of cotton/polyester fabric G with the lowest mass per square meter because of the very good physiological comfort parameters and the satisfactory sensorial comfort parameters.